Evaluation of Maternal and Fetal Stress Hormones During the Process of Birth - Burcu Kisa Karakaya; Ozlem Moraloglu; Rahime Bedir Findik; Necati Hancerliogullari; Hatice Celik; Tuba Candar; Halil İbrahim Yakut (Medical Network, 2018)
Objective: This study aims to determine whether mode of delivery is associated with the endocrine stress response in mother and newborn. Study Design: This prospective observational study was conducted with 86 women with a normal singleton pregnancy who delivered healthy infants between 37 and 41 weeks of gestation in a tertiary center. Study groups included; (1) women undergoing normal vaginal delivery with epidural anesthesia, (2) women undergoing vaginal delivery with immersion in water for pain relief during labor, (3) women delivered through elective caesarean section without labor. After delivery, thyroid stimulating hormone, cortisol, insulin, prolactin and Beta-endorphin levels were measured in maternal and umbilical cord serum and their relationships between modes of delivery were investigated. Results: It was found that the concentrations of cortisol and beta-endorphin after vaginal delivery with immersion in water group in both mothers and infants were higher than other two modes of delivery and these differences were statistically significant. Umbilical cord concentration of cortisol was the lowest in the caesarean section group. Conclusions: Maternal and fetal stress response was found to be associated with the mode of delivery and labor.